Associative Identification of Proper Names: A Cognitive Approach - Aleksieieva, Natalia (Տիգրան Մեծ)
A mental lexicon is a storage that holds the data about everything we know until it is required to be used. Onyms are stored in the mental lexicon in the form of concepts as individual units of knowledge which reflect the personal experience of the human being. The research aims to explore the standard ways of associative comprehension of proper names to better understand the essence and meanings they exhibit. The view substantiates that the transition from traditional to cognitive onomastic research will help to set-tle disputes among onomasticians and language philosophers as to the controversial subject of the seman-tic and referential status of proper names.In this research, the author conducts a free-associative experiment with 250 English native speakers. The result of the study was the conclusion that the ways of associative identification of onyms depend not only on our presuppositional knowledge, direct or indirect experience in connection to a certain proper name but also on a set of proprial and linguistic features peculiar to each name. The specificity of each proper name in this sense will determine the primary mechanism of its associative identification.
Keywords: Linguistics